Eight homodinuclear lanthanide complexes prepared from a quinoline based ligand: structural diversity and single-molecule magnetism behaviour. (7th March 2018) - Pan, Yangdan; Zhang, Haifeng; Qin, Yaru; Ge, Yu; Cui, Yanfeng; Li, Yahong; Liu, Wei; Dong, Yaping
Abstract : Eight dinuclear complexes are prepared and characterized; complex6 exhibits SMM behavior with a U eff value of 14.83 K. Abstract : Eight dinuclear lanthanide complexes of compositions [Pr2 L2 (NO3 )4 (H2 O)]·EtOH (1 ), [Nd2 L2 (NO3 )4 (CH3 CN)]·CH3 CN (2 ), [Sm2 L2 (NO3 )4 (CH3 CN)]·CH3 CN (3 ), [Eu2 L2 (NO3 )4 (H2 O)] (4 ), [Tb2 L2 (NO3 )4 ] (5 ), [Dy2 L2 (NO3 )4 ] (6 ), [Ho2 L2 (NO3 )4 ] (7 ) and [Er2 L2 (NO3 )4 ] (8 ) (HL = 2-{[(2-hydroxy-3-methoxybenzyl)imino]methyl}quinoline-2-formaldehyde) have been synthesized by reactions of Ln(NO3 )3 ·6H2 O with a tetradentate quinoline-based Schiff base ligand (HL) in MeCN/EtOH/NEt3 solution. The structures of1–8 are characterized by X-ray single crystal diffraction analysis. They exhibit four distinct structures. In complex1, two Pr III atoms are triply bridged by three oxygen atoms, including an unusual water bridge. Complexes2 and3 are isostructural, in which two metal centres are nine- and ten-coordinated, respectively. There are two characteristic Eu III ions in4, which are eight- and ten-coordinated, respectively. In the isomorphous compounds5–8, the two Ln III atoms in the centrosymmetric molecules are doubly bridged by phenolate oxygen atoms and both metal ions possess nine-coordinate environments. Dc magnetic susceptibility studies in the 2–300 K range were performed for compounds6 and7 . Antiferromagnetic interactions were determined for these two complexes. Complex6 shows slow magnetic relaxation behaviour with an energy barrier ( U eff / K B ) of 14.3 K.